Regional University: Guidelines for Self-Renewal - N. G. Bazhenova (Высшее образование в России)
The article presents the history of formation, current state and prospects of development ofSholom-AleichemPriamurskyStateUniversityas the main guidelines for self-renewal of the regional University. The issues of self-renewal and self-development of the organization are viewed through strategic projects and implementation of a change management model. The development of the territorial entity of theRussian Federationis impossible without the development of an educational cluster on its territory. After 50 years of existence of the Jewish Autonomous Region, it became necessary to develop higher education institutions for training personnel that could meet the internal needs of the socio-economic sphere of the region. The author describes external and internal factors that cause the processes of self-renewal of the education system. New challenges, objective demands of the region should be an integral part of the system of self-development of the regional University. A modern regional University as a self-developing system can and should become not just a “filter” for regional innovations, but also the most important tool for their promotion on the territory. It is able to generate new cohorts of active and qualified specialists, who are integrated into the region, grounded in it and able to create new areas of economic and social activities, new jobs. In this case, it is already a two-way process. Despite its dynamics of development,Sholom-AleichemPrimurskyStateUniversityremains a regional university whose strategic goal is to be an educational, research, innovation and cultural regional centre. It focuses on training highly qualified personnel and consolidating intellectual resources that can improve the quality of life, preserve and develop the culture of the Jewish Autonomous Region andRussiaas a whole in the Far Eastern region.